Architecture of first societies : a global perspective - Jarzombek, Mark (Hoboken, New Jersey : Wiley, 2013)
"Starting with the dawn of human society, through early civilizations, to the pre-Columbian American tribes, Architecture of First Societies: A Global Perspective traces the different cultural formations that developed in various places throughout the world to form the built environment. Looking through the lens of both time and geography, the history of early architecture is brought to life with full-color photographs, maps, and drawings. Drawing on the latest research in archaeological and anthropological knowledge, this landmark book also looks at how indigenous societies build today in order to help inform the past." -- Publisher website.
Introduction -- Part one : Foundations -- The human world -- Late Pleistocene-Early Holocene societies -- Savanna and forest peoples today -- The great northern continuum : part I -- The great northern continuum : part II -- The mound and plaza societies of the Americas -- Plants, animals, and rituals -- The first agro-pastoral perspectives -- Part two : transitions -- Village and chiefdom worlds -- Expansion into Europe -- Emergence of Central and South American agriculture societies -- Cattle-tending societies -- The world of portable architecture -- The oceanic horticultural continuum -- African transformations -- Agro-centrism in North America -- Coda : encounters with modernity -- Index.
Includes bibliographical references and index.
ARC
Keywords: Architecture, Prehistoric -- Textbooks; Antiquities, Prehistoric -- Textbooks; Dwellings, Prehistoric -- Textbooks; Architecture, Prehistoric -- Textbooks; Architecture, Prehistoric; Architecture; Textbooks